PENGARUH DEODORANT NIVEA TERHADAP PRESEPSI DIRI DAN KEPERCAYAAN DIRI PADA MAHASISWA/I FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Asima Winola Siahaan; Thalia Azka Ivani; Jihan Abiah Rahmah; Petrus Feraldo Sianipar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the relationship between the use of Nivea Deodorant on self-perception and self-confidence among Medan State University students. The research method used is quantitative using questionnaires via Google Form as a data collection instrument. A total of 55 Medan State University students who used Nivea deodorant were the research samples. The results of the research show that there is a positive and significant relationship between the use of Nivea Deodorant on self-perception and self-confidence among Medan State University students. This means that the use of Nivea Deodorant can increase self-perception and self-confidence in Medan State University students.